Parents' Educational Level Correlates with The Cognitive Development of Logical Thinking in Early Childhood - Putri, Leni Alifa; Darsinah, D (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The present study aims to contribute to the existing body of research on the relationship between family and cognitive development by examining the link between parental education levels and cognitive development in early childhood.Methodelogy: This study utilizes data concerning parents and students in the Kedungwuni subdistrict, specifically at Aisyiyah Puri Kindergarten and RA Muslimat NU Kwayangan, to ascertain the extent of the relationship between parental education and cognitive development in early childhood. The present study employed a descriptive qualitative method, with a sample size of 101. A direct questionnaire was administered to parents to ascertain their level of education, while children aged 5-6 years were asked to complete an indirect questionnaire containing cognitive development tests.Results: The findings indicated that children with highly educated parents exhibited higher levels of cognitive development in logical thinking compared to children with less educated parents. A correlation has been demonstrated between higher parental education levels and increased diversity in knowledge and experience, which can be applied in the future, particularly in enhancing logical thinking in early childhood. These results demonstrate a positive correlation between parental education levels and the cognitive development of logical thinking in early childhood. This study contributes to the existing body of knowledge by underscoring the pivotal role that parental education plays in shaping cognitive abilities in early childhood. This phenomenon also underscores the crucial role that higher education plays in adults' decision-making processes, particularly in the context of marital transitions.